2015
DOI: 10.1108/jeim-09-2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of knowledge management practices on organizational performance

Abstract: Purpose – The purpose of this paper is to present a holistic approach regarding evaluation of knowledge management (KM) practices on organizational performance. The effects of seven critical success factors (CSFs), namely leadership role, organizational culture, KM strategy, processes and activities, training and education, information technology, and motivation and rewarding system, on organizational performance in the framework of four perspectives of balance scored card (BSC) approach were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 49 publications
10
106
0
3
Order By: Relevance
“…The mean score for knowledge acquisition, as shown in Table 3, was (3.74) which reflect a strong positive correlation at a (.000) statistically significant level, as Table 4 indicates which supports the hypothesis. This results are similar to similar research results which revealed that KM practices positively and meaningfully impact overall organizational performance (Valmohammadi and Ahmadi, 2015;Akpotu and Lebari, 2014;Alnaweigah, 2013;Ababneh, 2008).…”
Section: Testing Hypothesessupporting
confidence: 81%
“…The mean score for knowledge acquisition, as shown in Table 3, was (3.74) which reflect a strong positive correlation at a (.000) statistically significant level, as Table 4 indicates which supports the hypothesis. This results are similar to similar research results which revealed that KM practices positively and meaningfully impact overall organizational performance (Valmohammadi and Ahmadi, 2015;Akpotu and Lebari, 2014;Alnaweigah, 2013;Ababneh, 2008).…”
Section: Testing Hypothesessupporting
confidence: 81%
“…on the four outcomes of BSC and finds that knowledge sharing can be used to predict the performance of internal processes and knowledge absorption can indicate and improve customer satisfaction levels. Valmohammadi and Ahmadi [30] study the impact of KM practices on organizational performances through a BSC approach and demonstrate that the impact is significant only on the dimension of growth and learning and insignificant on the other three dimensions of BSC outcomes. Combining the analytic network process (ANP) with a BSC, Hu et al [31] propose a framework to evaluate the performance of knowledge assets via the value of three indicators: labor, technology, and utilization.…”
Section: Papermentioning
confidence: 99%
“…Also, the researcher focused more on selecting articles that are very recent, thereby ignoring earlier studies which may carry information that is very vital for the study. Therefore, the researcher acknowledges these limitations by cautiously forming interpretations and conclusions that will not suggest a strong claim (Valmohammadi, & Ahmadi, 2015).…”
Section: Methodsmentioning
confidence: 99%